(untitled) (Al-Academy, 2022)
The research is exposed to the concept of rough discourse in contemporary theater with a critical reading that takes the genealogical work as a starting point in deconstructing the references of rough discourse and pursuing its paths in the civilization and cultural framework and how it identifies aesthetically within the theatrical field and the extents of its procedural treatments in order to reveal it and clarify its limits and representations, as the research included the first chapter. (methodological framework), the second chapter (theoretical framework), which included two sections, the first took place under the title (rough dramatization), while the second topic took place under the title (rough drama), and the second chapter resulted in indicators, and the third chapter was represented by the research procedures, as The researcher chose (the play YES GODOT) a model that is consistent with the research trends and its scientific and methodological nature, while the fourth chapter is reinforced with results and conclusions, sources and references and a summary of the research in English. The following are the main results and conclusions of the research